Urgency of the Qur’an Memorization Program in Shaping the Character of Urban Communities - Nikmatus Sholihah; M. Yunus Abu Bakar (Maharot : Journal of Islamic Education, 2025)
This study examines the urgency of Qur’an memorization programs in urban communities through a qualitative library-based approach, employing thematic analysis of relevant academic sources. Modernization and secularization in urban environments have significantly influenced the spiritual and moral orientation of younger generations, thereby creating increasingly complex challenges in character formation. The results of the literature review indicate that Qur’an memorization programs play a strategic role in shaping Qur’anic character through the internalization of religious values and moral development. The implementation of these programs has evolved into various models, including tahfidz houses, integrated Islamic schools, and digital tahfidz communities, with their effectiveness influenced by family support, educator competence, facility readiness, and adaptability to the digital environment. The main challenges identified include limited participant time, inadequate supporting facilities, and pressure from a less conducive digital culture. Therefore, strengthening tahfidz programs in urban areas requires strategic institutional management, enhanced educator capacity, targeted integration of digital technology, and supportive public policies. This research contributes to the field of Islamic education by reinforcing the conceptual understanding of the strategic role of tahfidz al-Qur’an in shaping Qur’anic character within urban society.